Math Teachers Come From the Darnedest Places: Adult Learners Becoming Adult Teachers - Gary L. Wright (Adult Education Research Conference, 2010)
In this qualitative study I sought a better understanding of the experiences of mathematics educators who, prior to engaging with their chosen profession, participated in a developmental mathematics course or program. The purpose was to learn more about (i) the impact of faculty (or institutional) attitudes and behaviors on these individuals and (ii) the factors, inside or outside the classroom, that supported their decisions to pursue careers in academia.